Some factors affecting the prosperity of trade in Ethiopia, 14th–18th Centuries - Mengistie Zewdu Tessema; Wondemeneh Adera Ayalew (Cogent Arts & Humanities)
Trade has long been one of the significant economic activities in the Ethiopian region and the Horn of Africa. However, some challenges had been hampering the development and prosperity of the trade. Thus, the main purpose of this article is to explore factors that affected the development and prosperity of trade in Ethiopia between the 14th and the 17th centuries. To carry out this study, both primary and secondary sources are employed. Using thematic analysis, a qualitative research approach, the study attempts to explore the factors that handicapped the development of trade in Ethiopia in the period understudy. This study revealed that the underdevelopment of trade during the period was not associated to a single factor. Rather factors like negative social attitude toward trade; the state’s limited control over the origin of items of trade; uncertain access to the Sea; the shift in the diplomacy of the state and limited diversity in the items of trade; and the absence of currency had contributed for the underdevelopment of trade. Thereby, this article argues that the limited growth of trade is associated with multiple factors which were hampering the commercial sector from attaining its utmost level of prosperity.